Multiple‐Aetiology Enteric Infections Involving Non‐O157 Shiga Toxin‐Producing Escherichia coli – FoodNet, 2001–2010. (1st February 2014) - Luna‐Gierke, R. E.; Wymore, K.; Sadlowski, J.; Clogher, P.; Gierke, R. W.; Tobin‐D'Angelo, M.; Palmer, A.; Medus, C.; Nicholson, C.; McGuire, S.; Martin, H.; Garman, K.; et al.
Summary We describe multiple‐aetiology infections involving non‐O157 Shiga toxin‐producing Escherichia coli (STEC) identified through laboratory‐based surveillance in nine FoodNet sites from 2001 to 2010. A multiple‐aetiology infection (MEI) was defined as isolation of non‐O157 STEC and laboratory evidence of any of the other nine pathogens under surveillance or isolation of >1 non‐O157 STEC serogroup from the same person within a 7‐day period. We compared exposures of patients with MEI during 2001–2010 with those of patients with single‐aetiology non‐O157 STEC infections (SEI) during 2008–2009 and with those of the FoodNet population from a survey conducted during 2006–2007. In total, 1870 non‐O157 STEC infections were reported; 68 (3.6%) were MEI; 60 included pathogens other than non‐O157 STEC; and eight involved >1 serogroup of non‐O157 STEC. Of the 68 MEI, 21 (31%) were part of six outbreaks. STEC O111 was isolated in 44% of all MEI. Of patients with MEI, 50% had contact with farm animals compared with 29% (P < 0.01) of persons with SEI; this difference was driven by infections involving STEC O111. More patients with non‐outbreak‐associated MEI reported drinking well water (62%) than respondents in a population survey (19%) (P < 0.01). Drinking well water and having contact with animals may be important exposures for MEI, especially those involving STEC O111.